Changing behavior of Customers in buying Consumer durables An Analytical study of Nasik (Rural and urban) (International Journal of Food and Nutritional Sciences, 2023)
This study aims to delve into the evolving dynamics of consumer behavior in purchasing durable goods within the Nashik region. By examining factors such as socio-economic conditions, technological advancements, and changing lifestyles, the research seeks to understand the underlying shifts in consumer preferences and purchasing patterns.